G31(P) Big hands healing little hearts. (12th March 2018) - Harvey, MJ; Gracie, E; Garvey, L; Fraser, R; Cook, N; Smith, B; Peng, WKE; Spenceley, N
Abstract : Aims: The Healing Little Hearts charity provides Cardiac Surgery and Critical Care for children with congenital heart disease in low and middle-income countries. We report the outcomes of the 5th mission to the Hospital Universiti Sains Malaysia. Methods: A prospective, observational study in a Malaysian teaching hospital during a one week charity mission. The visiting charity team collaborated with local adult services to provide assessment, operative intervention and postoperative care to a paediatric cohort. Results: Twelve operations were undertaken for ten patients (table 1) with a median age of 3.4 years (IQR [2.3–5.8]) and weight 11.9 kg (IQR [9.1–14.5]). For those requiring cardiopulmonary bypass (CPB), median time was 107 min (IQR [92–150]) and cross-clamp (XC) time 73 min (IQR [49.2–98.5]). Fast-track extubation was performed in 70% with no reintubations. Post-operative morbidity was low and only patient 2 returned to theatre for additional procedures: delayed sternal closure and subsequent re-exploration. Case 3 was complicated by Junctional Ectopic Tachycardia, which resolved with medical management. The team performed the institution's first redo surgery and neonatal operation. The local cardiac surgeon led his first paediatric VSD closure and Tetralogy of Fallot repair. All patients were extubated and discharged, or eligible for ICU discharge prior to conclusion of the mission. Visiting PICU staff were resident 24 hours a day. The local ICU team were supported by twice daily PICU rounds, multi-disciplinary meetings and bedside teaching for nurses and trainees. The visiting Cardiologist undertook outpatient consultations, intra-and post-operative echocardiography and ECHO teaching. A morning lecture series delivered education to local trainees on topics including cardiac output, inotropes, heart failure and the surgical management of congenital heart disease. Conclusions: Healing Little Hearts provides cardiac surgical and critical care in developing countries. Short, well-planned missions can deliver quality care to a high turnover of patients with safe, early extubation and minimal morbidity, despite limited resources. Future missions will provide ongoing training and support the development of a safe, independent program capable of handling carefully selected paediatric congenital cardiac surgeries.